Pengaruh Budaya Organisasi Terhadap Employee Engagement, Kinerja Dan Loyalitas Pegawai Pada Generasi Milenial PT Tirta Sukses Perkasa, Departement Packaging - Moch Adji Santoso; Nuraeni Nuraeni; Khoirul Huda (Politeknik Kampar, 2023)
The purpose of this study was to find out and measure the effect of organizational culture on employee engagement, performance and employee loyalty in the millennial generation (PT Tirta Sukses Perkasa, Packaging Department). The selection of the research sample used a saturated sample technique of 100 respondents, and was obtained at PT Tirta Sukses Perkasa, Packaging Department. For statistical tests and data processing is done using Partial Least Square (SmartPLS 4). The results showed (1) Organizational Culture has a significant positive effect on employee engagement. (2) Organizational Culture has a significant positive effect on employee performance. (3) Organizational Culture has a significant positive effect on employee loyalty. (4) Employee Engagement has a significant positive effect on employee loyalty. (5) Employee performance has a significant positive effect on employee loyalty.